Science Adaptive Assessment Tool: Kolb’s Learning Style Profile and Student’s Higher Order Thinking Skill Level - Zulfiani, Z.; Suwarna, I. P.; Sumantri, M. F. (Jurnal Pendidikan IPA Indonesia, 2020)
This study aims to determine studentsÃ¢â‚¬â„¢ profiles of learning styles, levels of higher-order thinking skills, and the effect of differences in studentsÃ¢â‚¬â„¢ competence to various HOTS instruments using the Science Adaptive Assessment Tool application. In this study, researcher used the descriptive survey approach. The subjects of this study were 251 students of grade 8 (Al-Zahra Indonesia Secondary school and MTsN 1 South Tangerang (Islamic Secondary school) academic year of 2019/2020. The research instrument used was a test to measure 21st century skills (HOTS), which varied on the learning styles of students studying natural science (Biology and Physics). The instrument was validated by expert judgment and empirically tested in order to obtain instrument reliability of learning style with adequate to high category variations. The results shows: (1) the profile of the most popular student learning styles is the assimilator (27,50%), while at least it is converger (20,71%); (2) Females tend to have assimilator learning style pattern, while males tend to have an accommodator learning style; (3) The higher-order thinking skills level in the Biology material was moderate (an average score of 39,69 from a maximum score of 70). The physics subject is in the lower category (an average score of 21,28 from a maximum score of 70); (4) The achievement of the HOTS score was influenced by the type of learning style and had average of a very small correlation, (5) There was significant difference incompetence across the KolbÃ¢â‚¬â„¢s learning stylesÃ¢â‚¬â€divergers, assimilators, convergers, and accommodators with the use of various HOTS instruments.